infrastructure - Grigoryeva, Elena (project baikal, 2021)
The darkness that came from the Mediterranean Sea covered the city hated by the procurator... М. Bulgakov. The Master and MargaritaThe seventh airfield subzone covered our beloved city. Construction was stopped, and engineering was frozen. Now we have as much free time as we need. And while Irkutsk is struggling with the mistakes of previous administrations, let's see how new air terminals are opened one by one in the regional capitals of the country: Kemerovo, Saratov, Perm... The first one we saw was LEONOV in Kemerovo. And we saw it not online, but live, when we arrived at the Festival “Zodchestvo in Siberia”.The object of the issue is not a frequent section in PB. This issue contains several significant infrastructure facilities by Moscow authors. Airport terminals in three Russian regional capitals (41) and the Nizhegorodskaya transport hub in Moscow (63).The main Siberian festival of this autumn is a regular festival “Zodchestvo in Siberia” held in the first decade of September in Kemerovo (15-36). It is noteworthy that the main focus of the work of the key speakers of this festival, Nikolay Shumakov and Timur Bashkaev, is on transport infrastructure facilities. So the stars are aligned for us to talk about it, about INFRASTRUCTURE.The infrastructural crisis has hit fully half of the inhabited world. The gigantic transport, energy and information systems created in the middle of the last century have exhausted their resources. Mikhail Mishustin's government is adopting an ambitious plan to invest tens of trillions of rubles into the country's infrastructures. Joe Biden's government is discussing a similar plan that costs trillions of dollars. Meanwhile, it turns out that both the philosophy and methodology of infrastructure design have fundamentally changed and now require a deep rethinking. Along with the burning issues, however, we do not forget about anniversaries. The new issue of PB opens with a diptych devoted to the 80th anniversary of our regular author Alexander Rappaport.
Keywords: air terminals; transport hub; festival; infrastructural crisis